Diagnosis and characterization of malignant effusions through pleural fluid cytological examination. Issue 4 (July 2019) - Porcel, José M.
Abstract : Purpose of review: Malignancy accounts for a substantial proportion of pleural effusions, and cytologic examination of pleural fluid is the easiest way to establish the diagnosis. This review summarizes relevant advances in the diagnostic cytopathology of pleural effusions for the practicing pulmonologist. Recent findings: Cytologic analysis using a stained smear and cell block preparation is able to provide the diagnosis in about 55% of malignant effusions. Processing a maximum of two separate specimens (provided the initial examination is negative) with an approximate volume of 40 ml each is the most accepted recommendation. Cytologic identification of mesothelioma is particularly challenging, but testing for BAP1 nuclear expression (immunocytochemistry) and p16 deletion (fluorescence in situ hybridization) has greatly improved our diagnostic capabilities. Similarly, in patients with advanced nonsmall cell lung cancer a comprehensive molecular testing on pleural fluid samples, which should include at a minimum epidermal growth factor receptor/v-raf murine sarcoma viral oncogene homolog B/anaplastic lymphoma kinase/reactive oxygen species 1/programmed death-ligand 1 alterations, is highly advocated to identify patients who may benefit from targeted therapies. Summary: A judicious use of pleural fluid cytologic specimens, which includes immunocytochemistry and molecular testing, eliminates the need for more invasive tissue sampling.